Risk Analysis in Salted Fish Agroindustry in Pusong Baru Village, Lhokseumawe City - Muhammad Authar ND; Sakral Hasby Puarada; Barmawi Barmawi; Cut Rozana Sari (SAINTIS Publishing, 2025)
The salted fish agroindustry is one of the important economic activities for coastal communities in Lhokseumawe City, especially in Pusong Baru Village. This activity plays a role in increasing the added value of fishery products, but in its implementation it is faced with various risks that can affect business sustainability. These risks include production risk, market risk, and financial risk. This study aims to analyze the type and level of risk in the salted fish agroindustry in Pusong Baru Village, Lhokseumawe City. The research method used is a case study method with a descriptive approach. Data was collected through interviews, observations, and questionnaires to salted fish agroindustry players. Risk analysis is carried out by assessing the probability and impact of the risk, then mapping the level of risk using a risk matrix. The results of the study show that production risk and market risk are the highest level of risks, especially related to dependence on weather conditions and selling price fluctuations. Therefore, an appropriate risk management strategy is needed to support the sustainability of the salted fish agroindustry.